Navigating Acute Stroke: Perspectives from Survivors, Caregivers, and Healthcare Professionals in Ireland During COVID-19: A Qualitative Study - Burton E; Hartigan I; Buckley CM; Kearney PM; Masterson S; Merwick Á; Mc Carthy VJC; Fleming A (Journal of Multidisciplinary Healthcare)
Edel Burton,1 Irene Hartigan,2 Claire M Buckley,1 Patricia M Kearney,1 Siobhan Masterson,3– 5 Áine Merwick,6,7 Vera JC Mc Carthy,2 Aoife Fleming8 1School of Public Health, University College Cork, Cork, Ireland; 2School of Nursing and Midwifery, University College Cork, Cork, Ireland; 3National Ambulance Service, Health Service Executive, Dublin, Ireland; 4College of Medicine and Health, University College Cork, Cork, Ireland; 5Discipline of General Practice, University of Galway, Galway, Ireland; 6Department of Neurology, Cork University Hospital, Cork, Ireland; 7School of Medicine, University College Cork, Cork, Ireland; 8Pharmaceutical Care Research Group, School of Pharmacy, University College Cork, Cork, IrelandCorrespondence: Edel Burton, School of Public Health, University College Cork, Western Gateway Building, Western Road, Cork, T12XF62, Ireland, Tel +353 (0)21 420 5500, Email edel.burton@ucc.iePurpose: Evaluating time-sensitive conditions like acute stroke and transient ischemic attack (TIA) provides insight into the impact of the COVID-19 pandemic on healthcare access and delivery. Our aim was to investigate the perspectives of stroke/TIA survivors, caregivers, and healthcare professionals, on the emergency/pre-treatment phase of acute stroke care in Ireland during the COVID-19 pandemic.Patients and Methods: During April-August 2023, we conducted semi-structured interviews with stroke/TIA survivors, caregivers and healthcare professionals involved in prehospital and hospital-based stroke care during the COVID-19 pandemic in Ireland (March 2020-February 2022). Participants were purposively sampled from four hospitals and one ambulance service region in the South of Ireland. Data analysis involved reflexive thematic analysis and patient journey mapping.Results: Thirty participants were interviewed: eight stroke/TIA survivors, seven caregivers and fifteen healthcare professionals (seven prehospital practitioners, four nurses, four doctors). Data analysis revealed five main themes: (i) Triage of stroke onset and transport to hospital; (ii) Treatment: navigating the hospital-based stroke pathway; (iii) Importance of time in stroke care; (iv) Navigating communication and connectivity in an era of COVID-19 risk and stroke care; (v) COVID-19 public health measures. These themes remained consistent across all three groups, although the depth of coverage varied. Patient journeys exhibited wide variation, with all groups noting the impact of COVID-19 on acute stroke/TIA care.Conclusion: This multi-stakeholder study revealed that the integrity of the acute stroke pathway remained intact during the COVID-19 pandemic. However, overall patient experience and willingness to seek care for suspected stroke or TIA were negatively impacted. Delays were observed across all stages of the stroke chain of survival during COVID-19, highlighting the importance of healthcare system resilience in this context. Additionally, it is important to consider how healthcare professionals can address the needs of individuals during times of increased demand on the healthcare system.Plain Language Summary: This study examines how the COVID-19 pandemic affected the treatment of acute stroke and transient ischemic attack (TIA) in Ireland. By exploring the experiences of stroke/TIA survivors, caregivers, and healthcare professionals, the study aimed to understand the impact on emergency and pre-treatment phases of stroke care.Between April and August 2023, we interviewed 30 participants: 8 stroke/TIA survivors, 7 caregivers, and 15 healthcare workers (including ambulance staff, nurses, and doctors) who were involved in stroke care during the pandemic. Participants were selected from four hospitals and one ambulance service in Southern Ireland. Data were analyzed to identify common themes and map out patient journeys. Stroke/TIA survivors and their families actively shaped the research throughout the study.Five main themes weredeveloped:Recognition of stroke onset and patient transport to the hospital.Navigation of the hospital-based stroke treatment pathway.The critical role of time in stroke care.Communication challenges and connectivity during COVID-19.Impact of public health measures related to COVID-19.All groups identified these themes, though their perspectives and depth of discussion varied. Patient experiences varied widely, with all participants noting COVID-19’s impact on stroke care.In conclusion, although the core stroke care process remained unchanged during the pandemic, patients were less likely to seek care promptly. Delays occurred at all stages of stroke treatment, highlighting the need for a healthcare system that can adapt and recover from challenges. Healthcare professionals should consider ways to address individual’s patient needs within the constraints of public health measures.Keywords: cerebrovascular disease, healthcare systems, health services research, patient journey, patient and public involvement, multi-stakeholder perspectives